RANCANG BANGUN INSTRUMEN DEHIDRATOR UNTUK PENGASAPAN DAN PENGERINGAN HASIL-HASIL PERIKANAN - Leksono, Tjipto; Hasan, Bustari; Zulkarnaini, Zulkarnaini (Jurnal Perikanan dan Kelautan, 2009)
Study on the dehydrator engineering for fish dehydration has beenconducted. The study was aimed to engineer, to built and to assess the existension,effectivity and efficiency of the fish dehydrator and the quality of dehydratedgiant catfish (Pangasius hypopthalmus) yielded by its application. The dehydratorhad three main chamber, namely: smoking furnace, smoking chamber, and dryingchamber. Its volume was measured 120 X 180 X 200 Cm3, and its smoking anddrying capacity were 100 kg.The result showed that both smoking and drying process could be aplliedsimultaneously. Therefore, the smoking fuel used could be saved. It spent 5kg/hour of coconut shell or 3.5 kg/hour of rubber wood (Hevea brasilliensis). Itwas not detected smoke contamination into the drying chamber. The rate oftemperature and RH in smoking chamber was 63o C and 43%, meanwhile, indrying chamber was 50o C and 49%. The consumer acceptance and the quality ofthe dehidrated fish yielded by smoking was not significantly different to it yieldedby drying. To get the maximum water content 40% in the fish, smoking processneeded 8 hours, meanwhile drying process needed 12 hours. The dehydrated fishcould be stored for 9 days at room temperature (30-32 oC).